2018
DOI: 10.3390/ijerph15091839
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Theory-Informed School-Based Intervention to Prevent Waterpipe Tobacco Smoking: Changes in Knowledge, Attitude, and Behaviors in 6th and 7th Graders in Lebanon

Abstract: Waterpipe tobacco smoking (WTS) is spreading worldwide. Research has indicated health consequences of WTS similar to cigarettes. Prevalence of WTS is high among young people. In Lebanon, current use rates of 35% have been documented among 13–15 year olds. We evaluated a school-based intervention. Method: We conducted a randomized-controlled-trial of a theory-informed WTS intervention. The intervention consisted of ten sessions based on social cognitive theory and the social influences approach. Thirty-one scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…For intance, Al-Mulla et al conducted a study to test the impact and feasibility of introducing a waterpipe prevention program to control the use of waterpipe among 7th and 8th graders in Doha. This study demonstrated the benefits of creating school-based interventions that can help delay or prevent initiation to waterpipe use [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For intance, Al-Mulla et al conducted a study to test the impact and feasibility of introducing a waterpipe prevention program to control the use of waterpipe among 7th and 8th graders in Doha. This study demonstrated the benefits of creating school-based interventions that can help delay or prevent initiation to waterpipe use [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short-term gains received an evaluation after 3 months of intervention and long-term benefits after 6 months of intervention [15], [16]. Tobacco consumption in this review is not only by traditional methods but also tobacco consumption in other forms such as waterpipe tobacco smoking or shisha, SLT, and betel quid or betel [17], [18].…”
Section: Resultsmentioning
confidence: 99%
“…The overall results of the study showed the effectiveness of school-based interventions proved by the increase in knowledge and attitude changes in all journal respondents. There is one journal that shows the results of increased knowledge and attitudes, but no change in behavior existed in the intervention group [17].…”
Section: Resultsmentioning
confidence: 99%
“…Another school-based hookah prevention program in Lebanon succeeded in enhancing the knowledge and shifting the students' attitude against hookah yet had no impact on behavior. Their failure to change behavior was attributed to the short study period, overall positive social context towards hookah, and weak anti-tobacco policy (39). Another important issue in hookah control programs is the lack of consensus on the need to design hookah-speci c interventions.…”
Section: Discussionmentioning
confidence: 99%